Evaluation of hemagglutinin, neuraminidase and matrix genes of Malaysian low pathogenic avian influenza virus strain H5N2 through comprehensive sequence analysis - Ahmad Rizal, Nurul Fatin Shafikah (2022)
The avian influenza viruses (AIV) of the H5 subtype have the ability to spontaneously mutate from low pathogenic (LPAI) to highly pathogenic (HPAI), which can cause high mortality in poultry. In 2004, H5N2 is an example of an LPAI strain that circulated in Malaysia. The sporadic activity of this strain was still observed in other countries, with HPAI H5N2 strain has been reported in Minnesota U.S. in 2015. Little is known about the pathogenic switching, apart from the mutation at the hemagglutinin cleavage site which significantly contribute to the phenomenon. Therefore, any other markers that could potentially confer pathogenic switching would be important to determine the pathogenicity of the virus. This study aims to propagate and determine infectivity of the Malaysian LPAI H5N2 virus, to amplify the hemagglutinin (HA), neuraminidase (NA), and matrix (M) genes, and to use bioinformatics software to analyse the obtained sequences. Upon H5N2 strain A/Duck/Malaysia/8443/2004 virus propagation in SPF eggs, the allantoic fluid was harvested and subjected to hemagglutination assay. Viral RNAs were extracted and amplified by RT-PCR prior to sequencing. Results showed successful amplifications of HA (1732 bp), NA (1431 bp) and M (1019 bp) genes, whereby the multibasic amino acid (aa) sequence at the HA cleavage site was not observed. Host-associated analysis detected one human-associated mutation Q78K at the M2 protein. The HA protein showed identical aa with HPAI reference strain at position 113 which is known to affect pathogenicity, but no D94N and N182K/D mutations, which influence the binding of human influenza receptor. The virus also showed less glycosylation sites, but similar aa sequence at the NA active sites. Known motifs that decrease the susceptibility of NA or M2 inhibitor drugs were not found. The phylogenetic tree showed that the virus was grouped within the Eurasian H5 lineage, and clustered with other AIV subtypes. These data demonstrate diverse characteristics of the Malaysian LPAI H5N2, compared to HPAI H5N2. Although it may be difficult to predict the LPAI to HPAI pathogenic switching effectively, the studied AIV exhibited no considerable markers that would signal a prospective transition to HPAI. This comprehensive sequence analysis will aid epidemiological research of the dynamics and evolution of circulating AIV in poultry.